A Scoring System for Patients With Gastro-Intestinal Stromal Tumor Based on Preoperative Abdominal Computed Tomography Scans Findings and Neutrophil-Lymphocyte Ratio as A Predictor for Malignancy Risk - Kusnadi, Dana Satria; Putranto, Agi Satria; Wibowo, Taufik Agung; Rahadiani, Nur; Kumalawati, July (http://dharmais.co.id/, 2025)
Background: The risk of malignancy in Gastrointestinal Stromal Tumors (GISTs) is currently determined based on the National Institute of Health (NIH) and the modified NIH consensus. Abdominal CT scans have been used to determine the characteristics of GIST; the neutrophil-to-lymphocyte ratio (NLR) has also been known to provide prognostic and predictive value in malignancies. In this study, we assessed and developed a scoring system for the malignancy risk of GIST patients based on CT scan findings and preoperative NLR values.Methods: This cross-sectional study was conducted using secondary data. CT scan findings include tumor size, location, shape, growth pattern, margins, contour, calcifications, ulceration, necrosis, organ invasion, vascular enlargement, lymphadenopathy, metastasis, and enhancement pattern. Malignancy risk data using histopathology results were obtained as a standard reference. Inclusion criteria comprised patients diagnosed with GIST through postoperative histopathology and immunohistochemistry, with complete preoperative contrast-enhanced CT scans and hematology test results. Subjects were excluded if they had incomplete data, very small tumors ( 0.5 cm), multiple GISTs or gastric cancer, infections (lung/urinary tract), or trauma at the time of NLR examination. Multivariate analyses were performed to identify predictors of malignancy risk. SPSS version 25 was used for data analysis.Results: A total of 57 subjects were included in the study. A cut-off point of 2.7 was obtained for the NLR value. Bivariate analysis showed that tumor growth patterns (p = 0.003), peritumoral vascular enlargement (p = 0.013), and high NLR values (p = 0.047) were associated with high malignancy risk. Further multivariate analysis showed exophytic growth pattern (p = 0.001, OR = 45.33), mixed growth pattern (p = 0.002, OR = 17.46), and high NLR (p = 0.010, OR = 8.95) as the predictors for malignancy risk. The scoring system using growth pattern and NLR was made with a maximum score of 3. Using a cut-off score of ≥ 2, the scoring system achieved a sensitivity rate of 77.19% and specificity of 81.25%.Conclusions: The malignancy risk of GIST can be assessed by evaluating tumor characteristics through preoperative abdominal CT scans and preoperative NLR value. A score of ≥ 2 based on tumor growth pattern and NLR can help clinicians to assess malignancy risk in GIST patients.